Exercise Intolerance, Benefits, and Prescription for People Living With a Fontan Circulation: The Fontan Fitness Intervention Trial (F-FIT)—Rationale and Design - Tran, Derek L.; Gibson, Hannah; Maiorana, Andrew J.; Verrall, Charlotte E.; Baker, David W.; Clode, Melanie; Lubans, David R.; Zannino, Diana; Bullock, Andrew; Ferrie, Suzie; Briody, Julie; Simm, Peter; et al. (Frontiers in Pediatrics, 2022)
Background: Despite developments in surgical techniques and medical care, people with a Fontan circulation still experience long-term complications; non-invasive therapies to optimize the circulation have not been established. Exercise intolerance affects the majority of the population and is associated with worse prognosis. Historically, people living with a Fontan circulation were advised to avoid physical activity, but a small number heterogenous, predominantly uncontrolled studies have shown that exercise training is safe - for unique reasons, may even be of heightened importance in the setting of Fontan physiology. The mechanisms underlying improvements in aerobic exercise capacity and the effects of exercise training on circulatory and end-organ function remain incompletely understood. Furthermore, the optimal methods of exercise prescription are poorly characterized. This highlights the need for large well designed, multi-center randomized controlled trials. Aims and Methods: The Fontan Fitness Intervention Trial (F-FIT-a phase III clinical trial - aims to optimize exercise prescription and delivery in people with a Fontan circulation. In this multi-center randomized controlled study, eligible Fontan participants will be randomized to either a 4-month supervised aerobic and resistance exercise training program of moderate-to-vigorous intensity followed by an 8-month maintenance phase; or usual care (control group). Adolescent and adult (≥16 years) Fontan participants will be randomized to either traditional face-to-face exercise training, telehealth exercise training, or usual care in a three-armed trial with an allocation of 2:2:1 (traditional:telehealth:control). Children (<16 years) will be randomized to either a physical activity and exercise program of moderate-to-vigorous intensity or usual care in a two-arm trial with a 1:1 allocation. The primary outcome is a change in aerobic exercise capacity (peak oxygen uptake) at 4-months. Secondary outcomes include safety, and changes in cardiopulmonary exercise testing measures, peripheral venous pressure, respiratory muscle and lung function, body composition, liver stiffness, neuropsychological and neurocognitive function, physical activity levels, dietary and nutritional status, vascular function, neurohormonal activation, metabolites, cardiac function, quality of life, musculoskeletal fitness, and health care utilization. Outcome measures will be assessed at baseline, 4-months, and 12-months. This manuscript will describe the pathophysiology of exercise intolerance in the Fontan circulation and the rationale and protocol for the F-FIT.